The theoretical study on nickel(II) amide complexes of carbon and carbene: new suggested molecules as fertilizers for plants - Ai Nhung, Nguyen Thi; Phuong Loan, Huynh Thi; Hoa, Le Thi; Hoa, Tran Thai; Duong, Tran; Tan, Vo Van; Hiep, Dang Tan; Tat, Pham Van; Quang, Duong Tuan (Vietnam Journal of Chemistry, 2015)
Quantum chemical calculations at the gradient-corrected (BP86) density-functional theory (DFT) with various basis sets (SVP, TZVPP, TZ2P+) are carried out to calculate for the first time the bonding situation of nickel(II) amide complexes of carbon Ni(NH2)2–C(PH3)2 (Ni2-CP2) and carbene Ni(NH2)2–NHCMe (Ni2-NHCMe). The nature of the (NH2)2Ni–C(PH3)2 and (NH2)2Ni–NHCMe bonds was analyzed with charge- and energy decomposition methods. The calculated equilibrium structure of carbon complex Ni2-CP2 shows that ligand C(PH3)2 (CP2) are bonded in a tilted orientation relative to the fragment Ni(NH2)2 with the bending angle, α, of Ni2-CP2 is 146.1°. In contrast to this, the carbene complex Ni2-NHCMe possesses end-on-bonded NHCMe ligand with the bending angle, α, is 180°. The bond dissociation energy (BDE) for the Ni2-CP2 bond is slightly higher than for the Ni2-NHCMe bond. The low-valent chemistry of nickel(II) amide in Ni2-CP2 always receives electrons from the s lone-pair orbital of C(PH3)2 and the Ni-C bond has a small contribution from (NH2)2Ni←C(PH3)2 π-donation. Although the carbon ligand has two lone-pairs orbitals for donation but the structure of carbon complex exhibits an unusual bonding at nickel(II) amide fragment. The EDA-NOCV results suggest that the CP2 ligand in the Ni2-CP2 is very strong s-donor and strong π-donor. The NHCMe ligand has only one lone pair for donation and the NHCMe ligand in the Ni2-NHCMe is strong s-donor and strong π-donor. The first results of this work not only give details the structures and chemical bonding of the molecules investigated, but also open up a field of research in the preparation of new molecules as fertilizers for plants. Keywords. Carbon, carbene, BDE; DFT; Bond dissociation energies (BDEs); Energy decomposition analysis (EDA); Natural Orbitals for Chemical Valence (NOCV)